Method for preparing carbon material from waste melamine resin and application
Through acid or alkali hydrothermal treatment and pyrolysis treatment of waste melamine resin, hydrothermal carbon materials and heteroatom doped carbon materials with good catalytic properties are prepared, which solves the problems of landfill pollution and high-temperature heat release of toxic gases, and achieves safe and environmentally friendly resource utilization.
Patent Information
- Application Number
- CN202411703580.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-03-14
AI Technical Summary
When dealing with waste melamine resin, landfills pollute the environment, high temperature and heat releases toxic and harmful gases, and chemical degradation products are difficult to separate.
The waste melamine resin is treated with acid or alkali hydrothermal treatment to separate the hydrothermal carbon material, and the heteroatom doped carbon material is obtained by pyrolysis, avoiding the generation of toxic gases.
The efficient conversion and comprehensive utilization of waste melamine resin is achieved, and the hydrothermal carbon materials and heteroatom doped carbon materials have good photocatalytic and electrocatalytic properties, and the process is safe and environmentally friendly.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a carbon material by utilizing waste melamine resin and application thereof, and belongs to the field of organic solid waste recycling and resource utilization. Background Art
[0002] Melamine resin, also known as melamine formaldehyde resin and melamine formaldehyde resin (melamine-formalde hyderesin, abbreviated as MF in English), is a cross-linked polymer obtained by the reaction of melamine and formaldehyde. Products required for different scenarios, such as dining cups and plates and children's toys, can be obtained through the compression molding process. In 2023, my country's melamine resin production will be 8 million tons, and the world's annual production is about 18 million tons. Although melamine resin products have high chemical stability, they will continue to release formaldehyde and melamine in the environment (Hunan Packaging 2009, (03), 3-6; Plastics Technology 2012, 40(09), 75-79; Molecules 2020, 25 (16), 3629). The landfill disposal of waste melamine resin may cause soil pollution or groundwater pollution.
[0003] The existing methods for recycling and treating waste melamine resin mainly include catalytic degradation and high-temperature pyrolysis. Among them, Hou Xianglin and Deng Tiansheng et al. used acid and alkali as catalysts to catalyze the degradation of waste melamine resin in an organic-water solution to obtain organic small molecule solutions such as melamine and cyanuric acid ( Green Chemistry 2021, 23 (19), 7816-7824; Green Energy gy & Environment 2024, 9 (5), 919-926; CN118063331A; CN111675827A; CN111747901A; CN111777566A; CN111808038A; CN111825626A; CN111875843A). However, the separation and purification of these small organic molecules are complicated, which is not conducive to large-scale application. The high-temperature pyrolysis method is to calcine the waste melamine resin to obtain carbon material ( Molecules 2023, 28 (4), 1772). This method is simple, but melamine resin is a thermosetting material and is prone to produce a variety of toxic and harmful gases (such as hydrocyanic acid) when calcined at high temperatures.
[0004] Therefore, it is urgent to develop a method for the efficient conversion and comprehensive utilization of waste melamine resin. At the same time, the generation of toxic and harmful gases should be avoided during the treatment process, and the obtained products should be easy to separate. Summary of the invention
[0005] Aiming at the problems of environmental pollution caused by existing landfill treatment, release of toxic and harmful gases by direct high-temperature pyrolysis and difficulty in separating chemical degradation products, the present invention provides a method for preparing carbon material by using waste melamine resin and its application.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing a carbon material using waste melamine resin comprises the following steps: (1) Grind the waste melamine resin and disperse it in water, add an acid or base catalyst, and fully react it in a closed container at 120-280°C for about 2-48 hours; (2) Separating the solid and liquid components, the solid phase is a hydrothermal carbon material that can be used for photocatalytic reaction; (3) After the liquid phase is evaporated and dried, it is calcined at 300-900°C under an inert atmosphere to obtain N,O-doped, N,O,P-doped, P,N,O,S-doped, or N,O,Cl-doped carbon materials, which can be used for electrocatalytic reactions.
[0007] In step (1), the acid or base catalyst is selected from inorganic acids such as H2SO4, HNO3, HCl, H3PO4, or organic acids such as p-toluenesulfonic acid, methanesulfonic acid, trifluoroacetic acid, or inorganic bases such as LiOH, NaOH, KOH, RbOH, CsOH, and aqueous ammonia solution.
[0008] In step (1), the molar concentration of the acid or base catalyst is C 0.006~1.00 mol∙L -1 .
[0009] In step (1), the ratio of waste melamine resin to water is R 0.5~0.01 g∙mL -1 .
[0010] In step (2), the solid and liquid components are separated, and the solid phase is a hydrothermal carbon material, which can be used as a photocatalytic reaction catalyst for photocatalytic hydrogen evolution or photocatalytic oxygen reduction to synthesize hydrogen peroxide.
[0011] In step (3), after the liquid phase is evaporated and dried, it is calcined at 300-900°C under an inert atmosphere to obtain N,O-doped, N,O,P-doped, P,N,O,S-doped, or N,O,Cl-doped carbon materials, which can be used as electrocatalytic reaction catalysts for electrolysis of water or oxygen reduction synthesis of hydrogen peroxide. The inert atmosphere is nitrogen, carbon dioxide or argon. The liquid phase volatilization temperature in the step is 25-60°C. During the evaporation process, auxiliary air bubbling is used to promote water evaporation and reduce material loss. Preferably, the drying temperature is 70-80°C. If the temperature is lower than 70°C, the drying is incomplete, and if the temperature is higher than 80°C, serious material loss will occur.
[0012] Preferably, the calcination temperature in the step is 300-900° C. When the temperature is lower than 300° C., the carbonization degree of the product is low and the conductivity is poor. When the temperature is higher than 900° C., the active sites of the product are lost and the activity of the product is significantly reduced.
[0013] Preferably, the calcination heating rate is 20-30°C∙min -1 The calcination time is 5 to 60 minutes. In the step, the calcination time is adjusted according to the calcination temperature. When the calcination temperature is 900°C, the calcination time is 5 minutes. When the calcination temperature is 300°C, the calcination time is 60 minutes.
[0014] The hydrothermal carbon material prepared by the above method can be used in photocatalytic hydrogen evolution or photocatalytic oxygen reduction to synthesize hydrogen peroxide.
[0015] The N,O-doped, N,O,P-doped, N,O,S-doped or N,O,Cl-doped carbon material prepared by the above method can be used in water electrolysis or oxygen reduction synthesis of hydrogen peroxide.
[0016] The present invention aims at the shortcomings of waste melamine resin landfill pollution, difficult separation of degradation products, and pyrolysis release of toxic gases, and develops a method for graded treatment and upgrading. Its advantages and beneficial effects are as follows: (1) waste melamine resin is hydrothermally treated with acid or alkali to separate high value-added hydrothermal carbon materials, and the liquid phase after hydrothermal treatment is pyrolyzed to obtain heteroatom-doped carbon materials. The acid or alkali used in the hydrothermal treatment does not need to be separated or post-treated, but is directly used for roasting treatment to adjust the heteroatom doping of carbon materials and promote the formation of porous and high-defect structures. Due to the presence of acid or alkali, the generation and emission of toxic gases (such as hydrocyanic acid) are effectively suppressed. (2) The obtained hydrothermal carbon material has good light absorption performance and exhibits excellent catalytic performance in photocatalysis; the obtained heteroatom-doped carbon material exhibits excellent performance in electrocatalysis due to doping, porosity and defective structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1This is a solid UV-visible-near infrared spectrum diagram of Example 1 of the present invention; Figure 2 This is a solid UV-visible-near infrared spectrum diagram of Example 3 of the present invention; Figure 3 is a SEM image of the melamine resin of the present invention; Figure 4 This is the SEM image of Example 1 of the present invention; Figure 5 This is the SEM image of Example 3 of the present invention; Figure 6 This is the SEM image of Example 13 of the present invention; Figure 7 This is the SEM image of Example 15 of the present invention; Figure 8 TEM image of Example 13 of the present invention; Fig. 9 TEM and EDX-Mapping images of Example 15 of the present invention. DETAILED DESCRIPTION
[0018] Below in conjunction with specific embodiment of the present invention, technical scheme of the present invention is clearly and completely described, obviously, described embodiment is only partial embodiment of the present invention, rather than whole embodiment. Reagent, method and equipment adopted in the present invention are conventional reagent, method and equipment in the art. Based on the embodiment in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work premise, all belong to the scope of protection of the present invention.
[0019] Example 1-10 is a hydrothermal preparation of hydrothermal carbon material from waste melamine resin Example 1
[0020] Disperse 1 g of waste melamine resin in 20 mL of water and add 125 µL of 65% concentrated HNO3 catalyst. R = 0.05, nitric acid concentration in aqueous solution C = 0.090 mol∙L -1 . The reaction was heated at 190 °C for 28 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 90 °C for 12 h, a brown hydrothermal carbon material with a mass of 0.32 g was obtained. The solid has good UV-visible-near infrared absorption in the range of 200-1200 nm ( Figure 1 , Figure 2 ). Compared with melamine resin ( Figure 3 ), the obtained hydrothermal carbon material exhibits a micron-spherical morphology ( Figure 4 , Figure 5 ). Example 2
[0021] Disperse 2 g of waste melamine resin in 200 mL of water and add 300 µL of 37% concentrated HCl catalyst. At this point, the ratio of melamine resin to water is R = 0.01, concentration of hydrochloric acid in aqueous solution C = 0.018 mol∙L -1 . The reaction was heated at 150°C for 40 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 90°C for 8 h, a yellow-brown hydrothermal carbon material with a mass of 0.8 g was obtained. Example 3
[0022] Disperse 5 g of waste melamine resin in 10 mL of water and add 50 µL of 98% concentrated H2SO4 catalyst. R = 0.5, sulfuric acid concentration in aqueous solution C = 0.092 mol∙L -1 . The reaction was carried out at 120°C for 48 hours. After the reaction was completed, the mixture was cooled to room temperature naturally and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 100°C for 6 hours, a brown hydrothermal carbon material was obtained with a mass of 2.4 g. Example 4
[0023] Disperse 8 g of waste melamine resin in 20 mL of water and add 500 µL of 85% concentrated phosphoric acid catalyst. R = 0.4, phosphoric acid concentration in aqueous solution C = 0.410 mol∙L -1 . The reaction was heated at 210℃ for 24h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 110℃ for 24h, a black-brown hydrothermal carbon material with a mass of 3.2 g was obtained. Example 5
[0024] Disperse 6 g of waste melamine resin in 15 mL of water and add 200 mg of p-toluenesulfonic acid catalyst. At this time, the ratio of melamine resin to water is R = 0.02, the concentration of p-toluenesulfonic acid in aqueous solution C = 0.077 mol∙L -1. The reaction was heated at 230℃ for 12 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 110℃ for 14 h, a dark brown hydrothermal carbon material was obtained with a mass of 3.4 g. Example 6
[0025] Disperse 10 g of waste melamine resin in 500 mL of water, add 100 µL of methanesulfonic acid and 100 µL of 65% concentrated HNO3 catalyst. R = 0.02, total concentration of mixed acid in aqueous solution C = 0.006 mol∙L -1 . The reaction was heated at 270℃ for 22 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 100℃ for 5 h, a reddish-brown hydrothermal carbon material with a mass of 6.1 g was obtained. Example 7
[0026] Disperse 4 g of waste melamine resin in 100 mL of water and add 0.05 g of sodium hydroxide catalyst. At this time, the ratio of melamine resin to water is R = 0.04, the concentration of sodium hydroxide in aqueous solution C = 0.013 mol∙L -1 . The reaction was heated at 280℃ for 2 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 120℃ for 5 h, a dark brown hydrothermal carbon material was obtained with a mass of 1.34 g. Example 8
[0027] Disperse 2 g of waste melamine resin in 30 mL of water and add 0.1 g of cesium hydroxide catalyst. At this time, the ratio of melamine resin to water is R = 0.067, cesium hydroxide concentration in aqueous solution C = 0.022 mol∙L -1 . The reaction was heated at 240℃ for 14 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 120℃ for 7 h, a dark brown hydrothermal carbon material with a mass of 0.7 g was obtained. Example 9
[0028] Disperse 5 g of waste melamine resin in 20 mL of water and add 0.5 g of potassium hydroxide catalyst. At this time, the ratio of melamine resin to water is R = 0.25, the concentration of potassium hydroxide in aqueous solution C = 0.446 mol∙L -1 . The reaction was heated at 250℃ for 12 h. After the reaction was completed, the mixture was cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 100℃ for 8 h, a dark brown hydrothermal carbon material with a mass of 3.4 g was obtained. Example 10
[0029] Disperse 10 g of waste melamine resin in 60 mL of water and add 1.5 g of lithium hydroxide catalyst. At this time, the ratio of melamine resin to water is R = 0.33, lithium hydroxide concentration in aqueous solution C = 1.04 mol∙L -1 . The reaction was carried out at 140°C for 26 h. After the reaction was completed, the mixture was naturally cooled to room temperature and centrifuged to obtain solid-liquid two-phase products. The solid phase product was washed three times with 50 mL of water and then dried at room temperature. After drying at 100°C for 10 h, a brown hydrothermal carbon material with a mass of 7.2 g was obtained.
[0030] Examples 11-12 are photocatalytic reaction performance Embodiment 11
[0031] In a closed reactor with a quartz window, 25 mg of the catalyst was suspended in 50 mL of pure water. The photocatalytic reaction was carried out under 300 W LED irradiation, with an oxygen pressure in the range of 0.1-1.0 MPa, a reaction temperature of 0-80 °C, and a reaction time of 2 h. The hydrogen peroxide production is shown in Table 1. The reaction results show that no hydrogen peroxide is generated when melamine resin is directly used as a catalyst. The obtained hydrothermal carbon materials all have good photocatalytic performance in producing hydrogen peroxide.
[0032] Example 12
[0033] 2 mg of the prepared photocatalyst was dissolved in 12 mL of triethanolamine aqueous solution (volume ratio V(TEOA):V(H2O) = 1:5), ultrasonically dispersed for 30 min, and transferred to a closed photocatalytic reactor, and argon was introduced for 30 min to remove the air. At a reaction temperature of 0-80 °C, a 300 W xenon lamp light source was used to simulate sunlight irradiation to carry out photocatalytic hydrogen evolution reaction. After 1 h of reaction, the hydrogen content in the gas was detected by gas chromatograph, and the dissolved hydrogen content in the solution was detected by hydrogen microelectrode. The total amount of hydrogen produced was added, and the hydrogen production is shown in Table 2. The reaction results show that no hydrogen is generated when melamine resin is directly used as a catalyst. The obtained hydrothermal carbon materials have good photocatalytic hydrogen production performance.
[0034]
[0035] Examples 13-23 are preparation of heteroatom-doped carbon materials from the liquid phase of waste melamine resin after hydrothermal treatment Embodiment 13
[0036] The liquid phase of Example 1 was evaporated by air bubbling at 25°C to obtain a yellow-brown viscous substance. Subsequently, it was dried in an oven at 70°C under reduced pressure for 12 h to obtain a yellow-brown solid powder with a mass of 0.35 g. Next, it was transferred to a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 900°C at a heating rate and calcined at this temperature for 5 minutes. After cooling to room temperature, N,O-heteroatom-doped carbon material powder was obtained with a mass of 0.1 g. High-angle annular dark-field transmission electron microscopy showed that the material exhibited a porous structure ( Figure 8 ).
[0037] Embodiment 14 The liquid phase of Example 2 was evaporated by air bubbling at 50°C to obtain a reddish brown viscous substance. Subsequently, it was dried in an oven at 75°C under reduced pressure for 6 h to obtain a reddish brown solid powder with a mass of 0.4 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 700°C at a heating rate and calcined at this temperature for 15 minutes. After cooling to room temperature, N, O, Cl- heteroatom doped carbon material powder was obtained, with a mass of 0.2 g.
[0038] Embodiment 15 The liquid phase in Example 3 was evaporated by air bubbling at 30°C to obtain a reddish brown viscous substance. Subsequently, it was dried in an oven at 80°C under reduced pressure for 12 h to obtain a reddish brown solid powder with a mass of 0.6 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 20°C∙min -1The temperature was rapidly raised to 500°C at a heating rate and calcined at this temperature for 30 min. After cooling to room temperature, N, O, S-heteroatom doped carbon material powder was obtained with a mass of 0.3 g. The electron energy spectrum element mapping results (EDX-Mapping) showed that C, N, O, and S elements coexisted in the material and were uniformly dispersed ( Fig. 9 ).
[0039] Example 16 The liquid phase of Example 4 was evaporated by air bubbling at 60°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 85°C under reduced pressure for 5 h to obtain a brown solid powder with a mass of 0.55 g. Next, it was transferred to a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 20°C∙min -1 The temperature was rapidly raised to 400°C at a heating rate and calcined at this temperature for 50 min. After cooling to room temperature, N, O, P-heteroatom doped carbon material powder was obtained, with a mass of 0.33 g.
[0040] Embodiment 17 The liquid phase of Example 5 was evaporated by air bubbling at 40°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 70°C under reduced pressure for 12 h to obtain a brown solid powder with a mass of 0.3 g. Next, it was transferred to a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 800°C at a heating rate and calcined at this temperature for 7 min. After cooling to room temperature, N, O, S-heteroatom doped carbon material powder was obtained with a mass of 0.12 g.
[0041] Embodiment 18 The liquid phase of Example 6 was evaporated by air bubbling at 50°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 75°C under reduced pressure for 5 h to obtain a brown solid powder with a mass of 0.54 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 600°C at a heating rate and calcined at this temperature for 20 minutes. After cooling to room temperature, N, O, S-heteroatom doped carbon material powder was obtained, with a mass of 0.24 g.
[0042] Embodiment 19 The liquid phase of Example 7 was evaporated by air bubbling at 50°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 70°C under reduced pressure for 12 h to obtain a dark brown solid powder with a mass of 0.45 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 20°C∙min -1The temperature was rapidly raised to 300°C at a heating rate and calcined at this temperature for 60 minutes. After cooling to room temperature, N,O-heteroatom doped carbon material powder was obtained, with a mass of 0.22 g.
[0043] Embodiment 20 The liquid phase of Example 8 was evaporated by air bubbling at 30°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 80°C under reduced pressure for 6 h to obtain a brown solid powder with a mass of 0.3 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 20°C∙min -1 The temperature was rapidly raised to 500°C at a heating rate and calcined at this temperature for 30 minutes. After cooling to room temperature, N,O-heteroatom doped carbon material powder was obtained, with a mass of 0.14 g.
[0044] Embodiment 21 The liquid phase of Example 9 was evaporated by air bubbling at 30°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 85°C under reduced pressure for 8 h to obtain a brown solid powder with a mass of 0.35 g. Next, it was transferred to a tube furnace. Under a nitrogen atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 600°C at a heating rate and calcined at this temperature for 20 minutes. After cooling to room temperature, N,O-heteroatom doped carbon material powder was obtained, with a mass of 0.17 g.
[0045] Embodiment 22 The liquid phase of Example 10 was evaporated by air bubbling at 40°C to obtain a brown viscous substance. Subsequently, it was dried in an oven at 80°C under reduced pressure for 10 h to obtain a brown solid powder with a mass of 0.42 g. Next, it was transferred to a tube furnace. Under an argon atmosphere, the mixture was heated at 30°C∙min -1 The temperature was rapidly raised to 800°C at a heating rate and calcined at this temperature for 7 minutes. After cooling to room temperature, N, O, S-heteroatom doped carbon material powder was obtained, with a mass of 0.26 g.
[0046] Embodiment 23 This example is a comparative example of Example 13, and the specific difference is that the melamine resin is directly calcined to prepare the heteroatom-doped carbon material. The specific process is as follows: 2 g of waste melamine resin is directly transferred to a tube furnace. Under a nitrogen atmosphere, the temperature is 30 ° C∙min -1 The temperature was rapidly raised to 900°C at a heating rate and calcined at this temperature for 5 minutes. After cooling to room temperature, N,O-heteroatom doped carbon material powder was obtained, with a mass of 0.5 g.
[0047] Examples 24-25 are electrocatalytic reaction performance Embodiment 24
[0048] The doped carbon materials obtained in Examples 13 to 23 were used as electrocatalysts. 5 mg of the doped carbon materials were dispersed in 1 mL of ethanol, and 10 µL of Nafion membrane solution was added to prepare catalyst ink. 100 µL of the ink was sprayed on a 2×2 cm 2 The gas diffusion electrode (working electrode) was prepared on conductive carbon paper, and the counter electrode and reference electrode were RuO2 / Ti-mesh and saturated calomel electrode, respectively. The electrolyte was 0.1 mol L -1 Potassium hydroxide solution. Oxygen was continuously introduced into the cathode of the gas diffusion electrolytic cell at a flow rate of 100 mL min -1 At 100 mA cm -2 The oxygen reduction was carried out to synthesize hydrogen peroxide at a current density of , and the yield is shown in Table 3. The experiment shows that the electrocatalytic hydrogen peroxide performance of Examples 13 to 22 is better than that of the directly calcined melamine resin of Example 23.
[0049] Embodiment 25
[0050] The doped carbon materials obtained in Examples 13 to 23 were used as electrocatalysts. 5 μL of ink was dropped onto a rotating disk electrode as a working electrode. The counter electrode and reference electrode were a platinum mesh electrode (Pt-mesh) and a saturated calomel electrode, respectively. -1 Potassium hydroxide solution, electrolyzed water under continuous argon flow. By measuring 10 mA cm -2 The overpotential of the working electrode under the current density was used to evaluate the catalyst activity, and the overpotential is shown in Table 4. The experiment shows that the water electrolysis performance of Examples 13 to 22 is better than that of the melamine resin directly calcined in Example 23.
[0051]
Claims
1. A method for preparing carbon material using waste melamine resin, characterized in that The following steps are involved: (1) Grind the waste melamine resin and disperse it in water, add an acid or base catalyst, and fully react in a closed container at 120-280°C; (2) Separating the solid and liquid components, the solid phase is a hydrothermal carbon material; (3) After the liquid phase is evaporated and dried, it is calcined at 300-900°C under an inert atmosphere to obtain N,O-doped, N,O,P-doped, N,O,S-doped, or N,O,Cl-doped carbon materials.
2. The method for preparing carbon material using waste melamine resin according to claim 1, characterized in that: In step (1), the acid or base catalyst is selected from inorganic acids such as H2SO4, HNO3, HCl, H3PO4, or organic acids such as p-toluenesulfonic acid, methanesulfonic acid, trifluoroacetic acid, or inorganic bases such as LiOH, NaOH, KOH, RbOH, CsOH, and aqueous ammonia solution.
3. The method for preparing carbon material using waste melamine resin according to claim 1, characterized in that: The molar concentration of the acid or base catalyst is 0.006-1.00 mol∙L -1 .
4. The method for preparing carbon material using waste melamine resin according to claim 1, characterized in that: The ratio of waste melamine resin to water is 0.5~0.01 g∙ mL -1 .
5. The hydrothermal carbon material prepared by the method of claim 1.
6. Use of the hydrothermal carbon material according to claim 5 in photocatalytic hydrogen evolution or photocatalytic oxygen reduction to synthesize hydrogen peroxide.
7. N,O-doped, N,O,P-doped, N,O,S-doped, or N,O,Cl-doped carbon material prepared by the method of claim 1.
8. Use of the N,O-doped, N,O,P-doped, N,O,S-doped or N,O,Cl-doped carbon material according to claim 7 in water electrolysis or oxygen reduction synthesis of hydrogen peroxide.
Citation Information
Patent Citations
Method for recovering melamine through catalytic degradation of melamine resin
CN111675827A
Method for selectively breaking C-N bond in melamine resin
CN111747901A
Two-step method for recycling melamine by degrading waste melamine resin
CN111777566A
Method for recovering cyanuric acid by catalytically degrading melamine resin
CN111808038A
Method for recycling cyanuric acid by degrading waste melamine resin through two-step method
CN111825626A